Bioleaching and biosorption of heavy metals from gold mine tailings by Aspergillus fumigatus in Penjom, Malaysia - Jalili Seh Bardan, Bahi (2012)
Mine tailings is an important source of heavy metal contamination in the environment. Decontamination of the mine tailings is necessary for the protection of the environment. In recent years, bioleaching process has gained increasing attention for extraction of metals from solid substrate, since it is simple, environmentally friendly and economical. The objectives of this study were (i) to characterize some physicochemical properties of gold mine tailings and to isolate and identify indigenous fungi from the tailings, (ii) to evaluate the ability of the indigenous fungus to bioleach heavy metals in step bioleaching and column bioleaching processes using distributed and surface applied techniques, and (iii) to assess the efficiency of A. fumigatus biomass to biosorb and remove metal from synthetic solutions and from leachate derived from a gold mine. Bioleaching experiments were conducted for the removal of heavy metals from mine tailings using a fungal strain isolated from the gold mine tailings and it was identified as A. fumigatus based on its 18S rDNA analysis. The bioleaching processes were carried out in one-step and spent medium leaching at 1%, 2%, 4% and 8% (w/v) tailing concentrations. Column bioleaching experiments were carried out to compare the effectiveness of the fungus to bioleach heavy metals from the tailings using distribution technique (DT) and surfaced applied technique (SAT). The ability of A. fumigatus to remove As, Fe, Mn, Pb and Zn from synthetic solutions and from leachate derived from gold mine during bioleaching was assessed. Batch sorption experiments were carried out to characterize the capability of fungal biomass (FB) and iron-coated fungal biomass (ICFB) to remove metal ions in single and multi-solute systems. Results showed that in the one step bioleaching process, production of oxalic acid was the highest among the other organic acids; while in the spent medium leaching citric acid was dominant. The removal of As, Fe, Mn and Zn was higher in the one step than the spent medium leaching but the reverse was observed for Pb. Heavy metals removal efficiency decreased with increasing concentration of tailings in both bioleaching processes. The column bioleaching study showed that DT produced higher oxalic acid than the SAT, therefore more As, Fe, Mn, and Zn were removed by the DT method compared to the SAT. However, Pb removal was low by DT than the SAT probably due to the precipitation of Pb as its oxalates. The DT was a more promising method for removal of metal ions from the mine tailings because distributing the fungus throughout the entire soil column improved the bioleaching efficacy of the heavy metals. The biosorption study showed that sorption data for all systems fitted well the Langmuir isotherm equation. The maximum sorption capacities of metals by both FB and ICFB were higher in the single metal system than the multi-solute system. It indicates that the presence of multiple metal ions in as solution suppressed adsorption of the individual metal ions. Sorption capacity of ICFB was higher than FB for all metal ions because the net surface charge of ICFB was more negative than FB at the pH range of 6 to 9, therefore the ICFB could adsorb more cationic metals. As for As adsorption, the As formed complexes with the Fe oxide of the ICFB surface sites. The FT-IR analysis showed that the functional groups of the fungal biomass were involved in the metal ions sorption. Overall, the results suggest that bioremediation process using A. fumigatus was effective for the leaching of heavy metals from mine tailings especially in the one-step bioleaching process using the DT method. The ICFB was found to be effective in adsorbing the metals present in the leachate of the tailing bioleaching process.